2011
DOI: 10.1002/hep.24355
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial cell specificity and apotope recognition by serum autoantibodies in primary biliary cirrhosis

Abstract: A major enigma of primary biliary cirrhosis (PBC) is the selective targeting of biliary cells. Our laboratory has reported that following apoptosis human intrahepatic biliary epithelial cells (HiBEC) translocate the E2 subunit of the pyruvate dehydrogenase complex immunologically intact into apoptotic bodies, forming an apotope. However, the cell type and specificity of this reaction has not been fully defined. To address this issue we have investigated whether PDC-E2, BCOADC-E2, OGDC-E2, four additional inner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 53 publications
1
49
0
Order By: Relevance
“…Panels of mouse monoclonal antibodies and human combinatorial autoantibodies against specific antigens, such as members of the ODC family [4,6,[25][26][27] or the gp210 antigen [19,28] , have been used in paraffin-embedded liver sections, and their significance in diagnosis and prognosis has been verified. Tsuneyama et al [4] have demonstrated that both AMApositive and AMA-negative PBC patients, but not controls, have abnormal expression of either PDC-E2 or a cross-reacting molecule in the apical region of the biliary epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Panels of mouse monoclonal antibodies and human combinatorial autoantibodies against specific antigens, such as members of the ODC family [4,6,[25][26][27] or the gp210 antigen [19,28] , have been used in paraffin-embedded liver sections, and their significance in diagnosis and prognosis has been verified. Tsuneyama et al [4] have demonstrated that both AMApositive and AMA-negative PBC patients, but not controls, have abnormal expression of either PDC-E2 or a cross-reacting molecule in the apical region of the biliary epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…6 We have previously demonstrated that apoptotic bodies from biliary epithelial cells contained the PBC-specific mitochondrial autoantigens. 26 Hence, within the liver, it is likely that biliary epithelial cells may produce exosomes that are critical for the homeostasis of biliary function 52,53 and we further hypothesize that exosomes released by damaged bile duct cells may augment this process. Indeed, since circulating exosomes can be internalized efficiently by APC (as shown in Figure 2), it is likely that such cells are involved in the processing and presentation of autoantigen to autoreactive T cells.…”
Section: Discussionmentioning
confidence: 84%
“…[11][12][13][14][15] Data from human studies and animal models demonstrate that the pathogenesis of PBC involves not only autoreactive T cells and other immune cells [16][17][18][19][20][21][22] but also biliary epithelial cells. 12,18,19,[23][24][25][26][27][28][29][30] Herein, we demonstrate that circulating exosomes from PBC could be taken up by antigenpresenting cells (APCs) and affect the expression of cell surface co-stimulatory molecules. We also demonstrate that circulating exosomes in PBC contain altered patterns of miRNA expression with elevated miRNA-451a and miRNA-642-3p compared to healthy adults.…”
Section: Introductionmentioning
confidence: 93%
“…Apoptosis is induced with bile salts as described previously [21][22], with minor modifications. Briefly, PKH-26-labelled or unlabelledHiBECs were incubated in culture medium containing 1 mM sodium glycochenodeoxycholate (GCDC; Sigma-Aldrich) at 37°C for 4 h. The apoptosis rate was assessed by flow cytometry after staining with 7-aminoactinomycin D (7-AAD) and fluorescein isothiocyanate (FITC)-annexin V (BD Biosciences, San Jose, CA, USA).…”
Section: Technique Of Apoptosis Induction and Bleb Isolationmentioning
confidence: 99%